Adherence to rehabilitation exercise and influencing factors among people with acute stroke: a cross-sectional study - Xing, Feng; Liu, Juan; Mei, Chang; Chen, Jingnan; Wen, Yi; Zhou, Jianrong; Xie, Shiqi (Frontiers in Neurology, 2025)
BackgroundPost-stroke rehabilitation exercise is recognized as the most effective and preferred intervention to reduce disability rates in patients. However, adherence to exercise is low among stroke patients. Previous research has mainly focused on the negative psychological factors influencing adherence, while the positive psychological aspects remain underexplored. Therefore, this study aims to investigate the factors influencing adherence to rehabilitation exercises in acute stroke patients, especially the positive psychological factors, in order to reduce the disability rate of stroke.MethodsFrom October 2023 to March 2024, a total of 227 patients with acute stroke were selected from a Grade-A hospital in Chongqing, China, using total sampling method. The patients’ general demographic data, Stroke Functional Exercise Adherence Questionnaire Scale (EAQ), Hospital Anxiety and Depression Scale (HAD), and Index of Subjective Well-Being Scale (IWB) were assessed. ANOVA, t-test analysis, correlation analysis, and multiple linear regression models were used to explore the influencing factors in people with acute stroke.ResultsThe total score for rehabilitation exercise adherence in acute stroke patients was 38.41 ± 11.13, corresponding to a mean adherence rate of 68.6%. Factors influencing adherence to rehabilitation exercise in acute stroke patients were identified, including age (p < 0.0001), presence of ICU stay (p = 0.03), National Institutes of Health Stroke Scale (NIHSS) score (p < 0.0001), and subjective well-being (p < 0.01).ConclusionAdherence to rehabilitation exercises in acute stroke patients was found to be medium. Our findings highlight that age, presence of ICU stay, and NIHSS score were found to have negative correlations with adherence. While a positive correlation was observed with subjective well-being.